Corporate reporting of intellectual capital: evidence from the Bangladeshi pharmaceutical sector. Issue 2 (1st July 2014) - Abhayawansa, Subhash; Azim, Mohammad
Abstract : Purpose: – The purpose of this paper is to provide an understanding of the intellectual capital (IC) reporting practices of the Bangladeshi pharmaceutical industry, one of the most significant industries to the Bangladeshi economy. It investigates the extent and qualitative characteristics of IC disclosures made by listed pharmaceutical companies in Bangladesh. Design/methodology/approach: – Data are gathered through a content analysis of the 2006 annual reports of 16 pharmaceutical companies quoted on the Dhaka Stock Exchange. The content analysis is performed by IC topic (i.e. categories and subcategories) and three semantic properties of IC disclosure: first, format (i.e. discursive, numerical but non-monetary, numerical-monetary and visual); second, news-tenor (i.e. positive, neutral and negative); and three, time-orientation (i.e. forward-looking, non-time-specific and past-oriented). Findings: – Results suggest a clear awareness among the Bangladeshi pharmaceutical companies of the significance of IC in corporate value creation and a commitment to publicly communicating IC. Some evidence is found of the need to manage stakeholder relationships, and legitimacy and impression management motives underpinning the management's desire to disclose IC. Also, proprietary cost theory explains the variation in the disclosure of types of IC. The Bangladeshi pharmaceutical companies did not adopt a consistent framework for IC reporting. A lack of consistency in reporting IC was also evident as the extent and subcategories of IC disclosures varied among companies. The findings indicate the Bangladeshi pharmaceutical companies may not have properly measured and managed their IC. Research limitations/implications: – There are two main limitations specific to this study. First, it only provides a snapshot of IC disclosure practices of Bangladeshi pharmaceutical companies in 2006. Changes may have taken place since then that would have affected the IC-intensity and IC utilisation of these entities. Second, the study's sample is limited due to its focus on one industry. However, it is representative of the population as it includes more than two-thirds of Bangladeshi pharmaceutical companies. This limitation affects the ability to conduct statistically meaningful analyses for testing any hypotheses relating to IC disclosure. Originality/value: – This is the first study on IC reporting practices of Bangladeshi pharmaceutical companies. Unlike most prior studies on IC disclosure practices, this study measures the quality of disclosures by analysing their semantic properties. The paper highlights the need for building organisational competencies in managing, measuring and reporting IC in Bangladesh.